Epidemiological studies of stem necrosis disease in potato caused by Groundnut bud necrosis virus - R.B. SINGH; V.S. PUNDHIR, MOHAMMAD ANSAR*, MOHD. AKRAM (Indian Phytopathology, 2015)
Stem necrosis disease causes serious reductions in tuber yield of potato (Solanum tuberosum L.). The causal agent of this disease is Groundnut bud necrosis virus (GBNV, genus Tospovirus). It is effectively transmitted by mechanical sap and insect vector, thrips (Thrips palmi) inoculation. Association of the GBNV with infected experimental potato host plants was detected by RT-PCR using specific primer pairs that targets NP gene. In vector transmission studies, minimum acquisition feeding period of 24 hrs and the minimum inoculation access period of 48 hrs were found. In screening of germplasm, out of 60 different accessions 50 genotypes were found to be infected by GBNV. Majority of plant showed necrotic lesions on stem followed by veinal necrosis. Out of two geographical locations, maximum disease index of 1.89 and 1.83 was found at ARS, Kota in early season ie. mid October planted tubers of two successive field experiments, respectively. The information generated in this study will help in understanding the dynamics of disease, transmission of virus, and range of disease effects on various germplasm.